ChemInform Abstract: A General and Efficient Method for the Alkoxycarbonylation of α‐Chloro Ketones. Issue 15 (25th March 2013) - Wahl, Benoit; Bonin, Helene; Mortreux, Andre; Giboulot, Steven; Liron, Frederic; Poli, Giovanni; Sauthier, Mathieu
Abstract The title reaction is extended to a wide variety of chloro ketones with different types of alcohols by using much lower catalyst loading than previously reported in the literature.